Discontinuous SVPWM Techniques for Balanced Two-Phase Three-Leg Voltage Source Inverter - Charumit, Chakrapong; Kinnares, Vijit (Journal of Advanced Development in Engineering and Science, 2023)
This paper describes the balanced phase voltage Discontinuous Space Vector PWM (DSVPWM) techniques for three-leg voltage source inverter (VSI) supplying balanced two-phase loads. Proposed DSVPWM strategy focuses on an analysis of switching losses by dealing with various types of zero space vector time in each switching sequence at high modulation index. The minimum of reduction in the switching losses will be occurred at 30 degrees lagging load power factor when compared with a continuous SVPWM technique. These proposed techniques are implemented on TMS320F28335 eZdsp for generating PWM gating signals of the switching devices in the main power circuit. The simulation and experimental results are given under conditions of switching losses and output current ripple to verify the correctness of the proposed principle.